PENGARUH TINGKAT PENGHASILAN, KUALITAS PELAYANAN FISKUS, DAN KESADARAN WAJIB PAJAK TERHADAP KEPATUHAN PEMBAYARAN PAJAK BUMI DAN BANGUNAN - Syafruddin Syafruddin (Universitas Riau Kepulauan, 2017)
This study examines the level of tax compliance in Batam city district by using several independent variables such as income levels , quality of service tax authorities and the taxpayer awareness. The purpose of this study was to analyze the effect of income levels, service quality, and taxpayer awareness of the compliance of land and building tax payments.The population in this study was based on data from the KPP Pratama Batam in 2012 as many as 58.595 SPPT propagated by NPWP. Sampling was done by the method Slovin. Number of samples was determined as 397 people. Primary data collection method used is by using questionnaires. Data analysis techniques used in this study is the technique of multiple regression analysis.Based on the results of the analysis carried out it could be concluded that the level of income and quality of service tax authorities do not have a significant positive effect on adherence property tax payments, but the taxpayer awareness variables have a significant positive effect on adherence property tax payments.